2001
DOI: 10.1017/s0952836901000322
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny and distribution of countershading in colonies of the naked mole‐rat (Heterocephalus glaber)

Abstract: Most naked mole-rats Heterocephalus glaber are countershaded, with purple-grey dorsal but pale pink ventral skin. The exceptions to this coloration pattern are uniformly pink, and include newborn pups, most queens and breeding males, and very old animals. Countershading begins to appear at 2±3 weeks of age and begins to disappear at c. 7 years of age. Countershading may provide camou¯age when young naked mole-rats are above ground attempting to disperse. Therefore, reproductives and older workers may lose this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Naked mole rat body temperature has been shown to vary with ambient temperature (Buffernstein & Yahav 1991), with countershading proposed as a mechanism that might help the mole rats maintain a constant body temperature. However, Braude et al (2001) found no evidence to suggest a role of thermoregulation for countershading in this species.…”
Section: Functions Of Countershadingmentioning
confidence: 64%
“…Naked mole rat body temperature has been shown to vary with ambient temperature (Buffernstein & Yahav 1991), with countershading proposed as a mechanism that might help the mole rats maintain a constant body temperature. However, Braude et al (2001) found no evidence to suggest a role of thermoregulation for countershading in this species.…”
Section: Functions Of Countershadingmentioning
confidence: 64%
“…Burtt (1981) proposed that dark dorsal coloration might serve for abrasion resistance (e.g. in bur-rowing animals), although a study of countershading in naked mole rats (Heterocephalus glaber, Ruppell, 1842) found little support for this hypothesis (Braude et al, 2001). DPD could also arise if selection for BM operates on only one surface of the body; for example, flatfishes exhibit DPD but, because of their benthic habit, would typically only be viewed from above.…”
Section: Introductionmentioning
confidence: 99%
“…Dark coloration on the back may also result from selection through protection from UV radiation (Braude et al . ). Both thermoregulation and UV protection may be better achieved through a uniform (dark) pigmentation.…”
Section: Introductionmentioning
confidence: 97%
“…Pigmentation will also affect thermoregulation by influencing the absorption of radiation (Braude et al 2001). The sun's rays most commonly strike dorsal parts of an animal, so darkening upper parts of the body could maximize heat gain from the sun and result in countershading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation